Romeo & juliet - Claybourne, Anna; Costa, Jana Shakespeare, William (Usborne ; EDC Pub. London, Tulsa, Okla., 2006)
Romeo and Juliet are in love-- but their families are bitter enemies. Set in medieval Verona, a place of sword fights, secrets and magic potions, their tragic love story plays out to a desperate end"--Page 4 of cover